Hepatic Legionella pneumophila Infection in an Infant With Severe Combined Immunodeficiency. Issue 4 (April 2018) - Lapidot, Rotem; Alawdah, Laila; Köhler, J. R.; Paulson, Vera; Levy, Ofer
Abstract : Rare cases of extrapulmonary involvement in Legionella spp. infections have been described, mostly in immunocompromised adults. We report a case of a 2-month old male with reticular dysgenesis variant of severe combined immune deficiency with multiple liver lesions. Core-needle biopsies of one liver lesion demonstrated Gram-negative bacilli and a broad-spectrum polymerase chain reaction assay detected Legionella pneumophila .